The invisible woman [videorecording (DVD)] - Fiennes, Ralph; Morgan, Abi; Jones, Felicity; Scott-Thomas, Kristin, 1960-; Hollander, Tom, 1967-; Tomalin, Claire (2014)
Nelly, a happily-married mother and schoolteacher, is haunted by her past. Her memories, provoked by remorse and guilt, take us back in time to follow the story of her relationship with Charles Dickens with whom she discovered an exciting but fragile complicity.